The impact of body mass index (BMI) on metabolic and endocrine parameters in women with the polycystic ovary syndrome (PCOS) - Edelstein, Sascha (Department of Obstetrics and Gynaecology, 2014)
Includes abstract. Includes bibliographical references (leaves 56-64).